2017
DOI: 10.1016/j.acmx.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava filters in pulmonary embolism: A historic controversy

Abstract: Objective: Rationale for non-routine use of inferior venous cava filters (IVCF) in pulmonary embolism (PE) patients. Methods: Thrombosis mechanisms involved with IVCF placement and removal, the bloodcontacting medical device inducing clotting, and the inorganic polyphosphate in the contact activation pathway were analyzed. In addition, we analyzed clinical evidence from randomized trials, including patients with and without cancer. Furthermore, we estimated the absolute risk reduction (ARR), the relative risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(81 reference statements)
0
6
0
Order By: Relevance
“… 25 IVCF implantation can not only prevent a fatal pulmonary embolism, but also provides a safety guarantee for interventional catheter thrombolytic therapy. 26 We believe that after thrombolysis, the stenosis of the deep vein lumen is more than 50%, and balloon dilation combined with stent implantation should be done with caution. The stent itself can cause damage to the inner wall of the blood vessel, produce an inflammatory reaction, or cause endothelial hyperplasia.…”
Section: Discussionmentioning
confidence: 96%
“… 25 IVCF implantation can not only prevent a fatal pulmonary embolism, but also provides a safety guarantee for interventional catheter thrombolytic therapy. 26 We believe that after thrombolysis, the stenosis of the deep vein lumen is more than 50%, and balloon dilation combined with stent implantation should be done with caution. The stent itself can cause damage to the inner wall of the blood vessel, produce an inflammatory reaction, or cause endothelial hyperplasia.…”
Section: Discussionmentioning
confidence: 96%
“…This approach has shown to be effective with a lower dose of the thrombolytic drug and shorter procedural time with no difference in major bleeding or recurrence 33 . As part of the thrombectomy procedure, we recommend the use of a prophylactic vena cava filter, as 17% of patients treated suffered asymptomatic PE demonstrated on computed tomography scans 34 . These filters should be removed as soon as possible 35 .…”
Section: Dvt Thrombolysis and Percutaneous Thrombectomymentioning
confidence: 99%
“…International and national guidelines 26,[27][28][29][30][31][32][33][34][35][36][37][38] recommend unfractionated heparin as adjunctive treatment and systemic thrombolysis in a well-selected (Table 5) 11 39 . The PEITHO study 40 and additional previous evidence have shown in-hospital improvement outcome, with systemic thrombolysis 14,16,17,19 in this group.…”
Section: Pe Thrombolysismentioning
confidence: 99%
“…International and national guidelines 26,[27][28][29][30][31][32][33][34][35][36][37][38] recommend unfractionated heparin as adjunctive treatment and systemic thrombolysis in a well-selected (Table 5) 11 39 . The PEITHO study 40 and additional previous evidence have shown in-hospital improvement outcome, with systemic thrombolysis 14,16,17,19 in this group.…”
Section: Pe Thrombolysismentioning
confidence: 99%